Is there a demand for multi-year crop insurance?. Issue 1 (5th May 2015) - Professor Lysa Porth and Professor ßKen Seng Tan, Assistant; Osipenko, Maria; Shen, Zhiwei; Odening, Martin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the aggregate demand for single- and multi-year crop insurance contracts and to discuss market potential for multi-year crop insurances. Design/methodology/approach – In this paper the authors develop a dynamic discrete choice model of insurance alternatives, in which single- and multi-year insurance contracts are offered to heterogeneous risk averse farmers. The farmers determine their insurances choices based on inter-temporal utilities. Findings – The results show that in a competitive insurance market with heterogeneous risk averse farmers, there is simultaneous demand for both insurance contracts. Moreover, the introduction of multi-year contracts enhances the market penetration of insurance products. Research limitations/implications – The effect of introducing multi-year crop insurance is moderate when applying the model to US corn production. In practice, however, the increase of insurance demand could be more pronounced because we did not consider marketing and administrative costs and thus ignore this cost reduction potential of multi-year insurance. Originality/value – This study adds to the literature analyzing the feasibility of multi-year crop insurance and also shows that there is market potential for multi-year crop insurance.